Evaluating the effectiveness of three national marine protected areas in the Yangtze River Delta, China - Zeng, Xu; Liang, Jun; Zeng, Jiangning; Chen, Mingyang; Zeng, Cong; Mazur, Makenzie; Li, Shenghui; Zhou, Zengjie; Ding, Wei; Ding, Peng; Cao, Ling (Frontiers in Marine Science, 2022)
China’s coastal areas face serious environmental degradation as a consequence of large-scale economic development. To balance environmental sustainability with economic development, China is currently implementing a strategy of ‘eco-civilization’, with marine protected areas (MPAs) expected to be one approach to achieving sustainable marine ecosystems. Since the 1990s, China has established over 270 MPAs, but their effectiveness remains unknown, particularly in the Yangtze River Delta. This study modified pre-existing frameworks to evaluate the effectiveness of three national MPAs in the Yangtze River Delta. The modified framework includes conservation outcomes and their potential drivers. Drivers consist of – attributes species or ecosystems within the MPA, attributes of the MPA, institutional design principles, and participation. Five scenarios were proposed based on score combinations of the four drivers: proactive, well designed, well governed, interactive, and learning. All three MPAs achieved a satisfactory level of outcomes and most of the drivers for all three MPAs achieved a satisfactory level. Two of the MPAs were categorized into the learning scenario, and the third into the well-designed scenario, indicating that there is still room to improve institutional design principles and public participation. We suggest developing cost and benefit indicators to more deeply understand proportionality among stakeholders. In addition, the role of participation should be clarified and promoted. We recommend regular environmental performance monitoring and assessment to identify problems and optimize management.